Polyoxometalates Facilitating Synthesis of Subnanometer Nanowires. (11th March 2021) - Zhang, Simin; Lu, Qichen; Yu, Biao; Cheng, Xijun; Zhuang, Jing; Wang, Xun
Abstract: Subnanometer nanowires (SNWs) refer to nanowires with diameters close to the size of a single crystal cell. SNWs show not only qualitative change in nature compared to the bulk materials or nanomaterials with larger size but also show several advantages in assembly and processing due to their polymer‐analog properties. However, the synthesis of SNWs is still a great challenge. Herein, a synthesis method of SNWs assisted by polyoxometalates is developed. Based on this method, several kinds of SNWs are prepared successfully, and the properties of the SNWs can be regulated efficiently and effectively, demonstrating the extensibility of this synthesis method. Among these SNWs, Bi2 O3 –PMoO SNWs show good photothermal conversion performance and can be processed into freestanding and flexible films through the wet‐spinning method. The Bi2 O3 –PMoO SNW films show good performance in solar steam generation and seawater desalination. The average stable evaporation rate can reach 1.38 kg m −2 h −1, and the efficiency is ≈ 91.1% under 1 sun illumination. The concentration of ions in the desalted seawater with the Bi2 O3 –PMoO SNWs film are reduced by four orders of magnitude, meeting the quality standards of drinking water and potential for practical utilization of solar energy in the seawater desalination. Abstract : A method of preparing subnanometer nanowires (SNWs) facilitated by polyoxometalates is developed. Based on this method, several kinds of SNWs are synthesized successfully, and the properties of the SNWs can be regulated effectively through controlling compositions or introducing new elements, demonstrating the extensibility of this synthesis method. It is useful for constructing functional SNWs.